Effectiveness of Lesser Known Homoeopathic Medicines in the Treatment of Iron Deficiency Anaemia (Advancements in Homeopathic Research, 2023)
Anaemia is a major public health problem in India  as it is estimated that most of the non-pregnant  women of reproductive age group are anaemic. It  occurs when there is decreased level of haemoglobin  in red blood cells. The primary cause of anaemia is  iron deficiency. Iron deficiency anaemia (IDA) may  be present with other systemic diseases. People with  mild and moderate iron deficiency anaemia may not  have any sign and symptom. But more severe iron  deficiency anaemia may cause fatigue, tiredness,  shortness of breath or chest pain. Although Homoeopathy gives importance to the  individualisation of the patients, for remedy selection,  still then, some medicines are prescribed based on  disease diagnostic features. Such medicines are not  well proved, so they are known as rare/lesser-known  medicines. Of course, their role in the management  of certain diseases cannot be ignored.  This article aims at showing the effectiveness of  some lesser-known medicines in the treatment of iron  deficiency anaemia.
Keywords: Homoeopathy; Iron deficiency anaemia; Lesser known drugs